Role played by Toll-like receptors 2 and 4 in lipoteichoic acid-induced lung inflammation and coagulation - Dessing, Mark C; Schouten, Marcel; Draing, Christian; Levi, Marcel; von Aulock, Sonja; van der Poll, Tom (The Journal of infectious diseases, 2008)
The cell wall of Streptococcus pneumoniae consists of lipoteichoic acid (LTA), which is released when pneumococci are killed by either the host immune system or antibiotic treatment. Release of excessive amounts of LTA has been implicated in the toxic sequelae of severe gram-positive infection by virtue of its proinflammatory properties. Several in vitro studies have shown that LTA is recognized by Toll-like receptor (TLR) 2 and CD14. Our objective here was to investigate the inflammatory properties of S. pneumoniae LTA in vivo and the role played by TLR2, TLR4, and CD14 therein. Wild-type (WT), TLR2 knockout (KO), TLR4 KO, TLR2x4 double-KO, and CD14 KO mice were intranasally inoculated with highly purified pneumococcal LTA. LTA induced a dose-dependent inflammatory response and activation of the coagulation and fibrinolytic pathways in a TLR2-dependent fashion. Surprisingly, TLR4 KO mice also displayed a somewhat diminished pulmonary inflammatory and coagulant response compared with WT mice, possibly as a result of absent TLR4 signaling through LTA-induced release of endogenous mediators. Pneumococcal LTA induces a profound inflammatory response and activation of the coagulation pathway in the lungs in vivo through a TLR2-dependent route, which likely is amplified by endogenous TLR4 ligands.